2019
DOI: 10.3389/fendo.2019.00088
|View full text |Cite
|
Sign up to set email alerts
|

Assay of Endogenous 3,5-diiodo-L-thyronine (3,5-T2) and 3,3′-diiodo-L-thyronine (3,3′-T2) in Human Serum: A Feasibility Study

Abstract: 3,5-diiodo-L-thyronine (3,5-T2) is an endogenous derivative of thyroid hormone with potential metabolic effects. It has been detected in human blood by immunological methods, but a reliable assay based on mass spectrometry (MS), which is now regarded as the gold standard in clinical chemistry, is not available yet. Therefore, we aimed at developing a novel ad-hoc optimized method to quantitate 3,5-T2 and its isomers by MS in human serum. Serum samples were obtained from 28 healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…This tight binding not only relates to their distribution proteins in blood, cells or tissues but especially also to surfaces of plastic material required during pre-analytical sample work and subsequent MS quantification. Recently, two groups reported for the first time 3,5-T2 serum concentrations determined by LC-MS. Lorenzini et al (75), observed a mean concentration range for 3,5-T2 in human serum of 78 ± 9 pM, while our own results (25) indicated that most human sera analyzed for 3,5-T2 have lower than 5 pM 3,5-T2 concentrations, which is the lower limit of quantification in our method. The fact that Lorenzini et al probably report higher LC-MS-based 3,5-T2 concentrations is due to the contamination of the 13 C 9-15 N -3,5-T2 internal standard, with "natural" unlabeled 3,5-T2.…”
Section: Alternative Lc-ms-based Approaches Are Needed To Determine Cmentioning
confidence: 43%
“…This tight binding not only relates to their distribution proteins in blood, cells or tissues but especially also to surfaces of plastic material required during pre-analytical sample work and subsequent MS quantification. Recently, two groups reported for the first time 3,5-T2 serum concentrations determined by LC-MS. Lorenzini et al (75), observed a mean concentration range for 3,5-T2 in human serum of 78 ± 9 pM, while our own results (25) indicated that most human sera analyzed for 3,5-T2 have lower than 5 pM 3,5-T2 concentrations, which is the lower limit of quantification in our method. The fact that Lorenzini et al probably report higher LC-MS-based 3,5-T2 concentrations is due to the contamination of the 13 C 9-15 N -3,5-T2 internal standard, with "natural" unlabeled 3,5-T2.…”
Section: Alternative Lc-ms-based Approaches Are Needed To Determine Cmentioning
confidence: 43%
“…Experiments in humans are indeed still limited, and, as discussed, it is not yet clear whether 3,5-T2 is produced in peripheral tissues at significant concentrations It is not completely understood, for example, whether blood concentrations of 3,5-T2 are related or not to intracellular concentrations of the hormone: It is possible that T3 deiodination to 3,5-T2 is controlled by tissue factors, differently regulated, for example, in a tissue-specific and/or in a metabolic state-specific manner. From this point of view, it is intriguing that no significant difference was found in serum 3,5-T2 of hypothyroid and hyperthyroid patients [202] and that no significant correlation was evidenced between serum 3,5-T2 and the main THs [203]. As mentioned, a further problem arises because of contamination by T3 of the commercial preparations of 3,5-T2, used as standards in the measurements [20,204].…”
Section: The Ins and Outs Of 35-t2 Researchmentioning
confidence: 93%
“…An antibody-based competitive chemiluminescence immunoassay (CLIA) [202] was used to investigate serum concentration of 3,5-T2 in humans under both physiological and pathophysiological conditions; the results suggested that 3,5-T2 concentrations do not differ in hyperthyroid (0.31 ± 0.02 nm) compared to hypothyroid (0.43 ± 0.04 nm) individuals [202]. More recently, HPLC coupled to tandem mass spectrometry [203] allowed a more accurate 3,5-T2 detection in human serum (the average concentration reported was 78 ± 9 picomoles/liter) [203]. In general, significant differences still remain among different detection methods.…”
Section: The 35-diodothyronine (35-t2) As a Hormonementioning
confidence: 99%
“…3,5-T 2 is present in significant concentrations in human serum [141] and seems to have important implications in the regulation of energy metabolism, with a direct effect on mitochondria as the most likely mechanism [139,[141][142][143] ( Figure 6). So far, serum 3,5-T 2 concentrations have been associated with some pathophysiological states in humans, mainly related to glucose and lipid metabolism [144]. This metabolite exerts thyromimetic activity, suppresses TSH and stimulates GH [145][146][147], though not as strongly as T 3 [139].…”
Section: Effects Of Estradiol On Tsh Cells In Males and Putative Chanmentioning
confidence: 99%